THE ABILITY OF STUDENTS OF LAW FACULTY IN ACADEMIC YEAR 2018/2019, ISLAMIC UNIVERSITY OF INDRAGIRI TO IDENTIFY PREPOSITION OF TIME IN A SENTENCE - Agus Mustajib (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2019)
Languages are not just sets of symbols. They also often conform to a rough grammar, or system of rules, used to manipulate the symbols. The grammar of a language is a complex and highly structured affair because it operates in terms of concepts and categories which have to be defined in the same way. So we need a grammar in using English and an understanding of the grammar also influences our ability in English. The students of Law Faculty 2018/2019, Islamic University of Indragiri are the students who are studying English in the first and second semester. So, the researcher is eager to know their ability to identify preposition of time in the sentences. The study focuses on the students’ ability in identifying preposition of time in a sentence especially “on, in, and at”. The number of the first semester of Law Faculty consists of three classes and the total of the students are 118 students. The populations are more than 100 students, so the researcher used a random sampling technique. The researcher can take the sample about 15% to 25% or more like the sample and the researcher take half of 100% is 50%. So, the samples of this research are 69 students. The researcher used a quantitative method to get the data needed. The research instrument in this research is to test and fill in the blank forms. The researcher used a sentence without preposition as the instrument of this research, because the students learned preposition through sentences. Based on the result of the test, the mean score of preposition was 63.98. It was categorized at a good level, which included in the interval 61-80. Where there are 6 students get in a very good score, 26 students get in a good score, 36 students get in enough score, 1 student get the poor score and there is no get in a very poor score. In conclusion, the students of Law Faculty 2018/2019 in identify preposition categorized nice and understand in the preposition.